Poly(d,l-lactide-co-glycolide) surface-anchored biotin-loaded irinotecan nanoparticles for active targeting of colon cancer - Giram, Prabhanjan S.; Nimma, Ramakrishna; Bulbule, Anuradha; Yadav, Amit Singh; Gorain, Mahadeo; Radharani, Nalukurthi Naga Venkata; Kundu, Gopal C.; Garnaik, Baijayantimala (ACS Omega, 2024)
A poly-(d,l-lactide-co-glycolide) (PLGA) copolymer was synthesized using the ring-opening polymerization of d,l-lactide and glycolide monomers in the presence of zinc proline complex in bulk through the green route and was well characterized using attenuated total reflectance-Fourier transform infrared, H-1 and C-13 nuclear magnetic resonance, gel permeation chromatography, differential scanning calorimetry, X-ray diffraction, matrix-assisted laser desorption/ionization time-of-flight, etc. Furthermore, PLGA-conjugated biotin (PLGA-B) was synthesized using the synthesized PLGA and was employed to fabricate nanoparticles for irinotecan (Ir) delivery. These nanoparticles (PLGA-NP-Ir and PLGA-B-NP-Ir) were tested for physicochemical and biological characteristics. PLGA-B-NP-Ir exhibited a stronger cellular uptake and anticancer activity as compared to PLGA-NP-Ir in CT-26 cancer cells (log p < 0.05). The accumulation and retention of fluorescence-labeled nanoparticles were observed to be better in CT-26-inoculated solid tumors in Balb/c mice. The PLGA-B-NP-Ir-treated group inhibited tumor growth significantly more (log p < 0.001) than the untreated control, PLGA-NP-Ir, and Ir-treated groups. Furthermore, no body weight loss, hematological, and blood biochemical tests demonstrated the nanocarriers' nontoxic nature. This work presents the use of safe PLGA and the demonstration of a proof-of-concept of biotin surface attached PLGA nanoparticle-mediated active targeted Ir administration to combat colon cancer. To treat colon cancer, PLGA-B-NP-Ir performed better due to specific active tumor targeting and greater cellular uptake due to biotin.